2012
DOI: 10.1007/s10903-012-9681-8
|View full text |Cite
|
Sign up to set email alerts
|

Geopolitical and Cultural Factors Affecting ARV Adherence on the US-Mexico Border

Abstract: BACKGROUND The data discussed represent the findings from a study by the NIH-funded Hispanic Health Disparities Research Center (UTEP), exploring the influence of institutional and psychosocial factors on adherence to antiretroviral medications (ARVs) by Mexican-origin persons living with AIDS on the US-Mexico Border. METHODS A qualitative approach was utilized consisting of clinic observations, baseline and follow-up interviews with patients (N=113), key informant interviews (N=9) and focus groups (5) with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…These data included: the social-normative environment (extent and type of information, and range of perceived alternatives and experiences that may affect social norms with implications for treatment adherence); the institutional environment of treatment/service delivery (meanings and significance that treatment options and experiences have for individuals and communities), and individual variation and culturally patterned behaviors and responses of patients (processes that affect how care seeking and adherence behaviors change). In comparing factors affecting adherence in the U.S.-Mexico border, the study included accounts of CAM use and offered insights and experience to support strategies and treatment on both sides of this border (Shedlin, Decena, and Beltran, in press). …”
Section: Introductionmentioning
confidence: 99%
“…These data included: the social-normative environment (extent and type of information, and range of perceived alternatives and experiences that may affect social norms with implications for treatment adherence); the institutional environment of treatment/service delivery (meanings and significance that treatment options and experiences have for individuals and communities), and individual variation and culturally patterned behaviors and responses of patients (processes that affect how care seeking and adherence behaviors change). In comparing factors affecting adherence in the U.S.-Mexico border, the study included accounts of CAM use and offered insights and experience to support strategies and treatment on both sides of this border (Shedlin, Decena, and Beltran, in press). …”
Section: Introductionmentioning
confidence: 99%
“…23 A 50% decline in medical tourism by Americans to Mexico was estimated in 2010 due to fear and increased border wait times due to stricter security checks. 24 Shedlin et al (2012) found decreased ability to cross the border due to violence as well as increased wait times and border security served as barriers to HIV care in El Paso. 25 Homedes (2012) notes although border crossing for healthcare may be reduced, the uninsured may continue to seek medical services in Mexico, choosing providers closest to the border to minimize danger.…”
Section: New Contribution To the Literaturementioning
confidence: 99%